Bibliometric analysis of tumor necrosis factor in post-stroke neuroinflammation from 2003 to 2021 - Zhao, Yang; Zhu, Qihan; Bi, Chen; Yuan, Jichao; Chen, Yujie; Hu, Xiaofei (Frontiers in Immunology, 2022)
Abstract Objective: Tumor necrosis factor (TNF), a crucial cytokine, has important research value in post-stroke neuroinflammation (PSN). We analyzed the studies that have been conducted in this area and used bibliometric methods to predict research hotspots and identify trends regarding TNF in PSN. Methods: Publications were accessed at the Science Citation Index Expanded 1975-2021 (SCI expanded), Web of Science Core Collection (WoSCC), on May 1, 2022. Additionally, software such as CiteSpace and VOSviewer were utilized for bibliometric analyses. Results: In total, 1391 original articles and reviews on TNF in PSN published from 2003 to 2021 were identified. An upward trend was observed in the number of publications on TNF in PSN. These publications were primarily from 57 countries and 1446 institutions, led by China and the United States with China leading the number of publications (NP) and the US with the number of citations (NC). The League of European Research Universities (LERU) and Journal of Neuroinflammation, respectively were the most prolific branches and journals. Zhang, John H. published the most papers and Finsen, Bente had the most cited papers. One paper by Kettenmann, H. published in 2011 reached the highest level of Global Citation Score (GCS). The keyword co-occurrence and reference co-citation analyses suggest that poststroke therapy and potential mechanistic pathways are important topics related to PSN in recent years. Reference burst detection suggests new burst hotspots after 2015, focusing on pathway modulation and discovery of therapeutic targets, suggesting a substantial development in the study of TNF in PSN research. Conclusion: The present bibliometric analysis shows a continuous trend of increasing literature related to TNF in PSN, and shows that TNF plays an important role in PSN involves multiple immune mechanisms and may contribute as a potential target for neuroprotective therapeutics after stroke. Prior to 2011, most of the research was focused on discovering the specific role of TNF in PSN, and in recent years studies have mainly targeted the exploration of the signaling pathways. Future research prospects may lie in finding key therapeutic targets in pathway of TNF in PSN. Keywords: Neuroinflammation; Stroke; TNF; Bibliometric analysis; VOSviewer; Citespace.